Clinical role of pulse oximetry in early detection of hypoxia among pilots during flight - R Eslami; K Emami; A Takzare (فصلنامه ابن سینا)
Background: A pilot’s hypoxia which may lead to dysfunction in some vital and sensitive organs can be detected and its prevention may greatly reduce the rate of aviation accidents. Therefore, this study aimed to investigate the prevalence of hypoxia using a pulse oximeter among pilots in an altitude chamber (hypobaric chamber).